The Paradox Of Interaction: "Unique" As Comprehensive (Transcendental Approach) - Харченко, Юлія Володимирівна (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Abstract. The paradox of the interaction of "unique", "universal" and "comprehensive" through the use of classical postulates of fundamental as well as philosophical and theological knowledge was examined in accordance with the aim of the study. The ideal interaction models were conceptualized, following the key task. It was confirmed a possibility of distinguishing the basic provisions in fundamental sciences: recognizing the reality of the existence of the world, patterns of its structure and the idea that the world can be cognizable by man. Within the key postulate in philosophy of “man – society – universe” interaction the categories of “man”, “society”, and “universe” were considered as ideal holistic constructions-singularities. Theological postulates were presented in the form of sacred texts reflected in the Revelation texts about the Comprehensive Logos; in the fundamental doctrine of the All-Powerful, Wise and All-Loving God, of His true essence and good deeds. The transcendental method was used to introduce a priori transcendental concepts – "unique", "comprehensive", "universal" which are a prerequisite for resolving the unique and universal interconditionality paradox, as well as their self-transcendence. In conclusion it was underlined that the points of view of a man as unique and divine as comprehensive and universal coincide precisely in the process of constructing the being of the social reality. That is, what a person does and creates is a predestination of the Comprehensive Logos.